Sosiodemografi Dengan Kepatuhan Peserta Prolanis Di Puskesmas Kedaton Bandar Lampung - Gayatri Putri Kinasih; Rita Agustina; Festy Ladyani Mustofa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Prolanis is an integrated proactive health service system that involves participants, Health Facilities and BPJS health in the context of health care for BPJS Health participants who suffer from chronic diseases including type 2 diabetes to achieve optimal quality of life. Objective: to determine the sociodemographic relationship with the compliance of PROLANIS participants at the Kedaton Bandar Lampung Health Center. Method: This research was an analytic observational study with cross sectional approach. Data sources of research data obtained from questionnaires and attendance book records of patients participating in PROLANIS at the Kedaton Health Center in Bandar Lampung. Population of 250 patients participating in PROLANIS. The sample consisted of 72 PROLANIST participants. Data collection in February 2020. Analysis through univariate and bivariate analysis. Results: that there was no relationship in age with results p = 0.09 (p> 0.05), sex with results p = 0.183 (p> 0.05) and there was a relationship in education with results p = 0.000 (p < 0.05), work with results p = 0.022 (p <0.05), family support with results p = 0,000 (p <0.05). The sociodemographic relationship with the compliance of PROLANIS participants at the Kedaton Health Center in Bandar Lampung. Conclusion: there is no relationship between age and gender with adherence to Prolanis and there is a relationship between education, employment, family support with adherence to follow Prolanis